(untitled) (Journal of Atomic and Molecular Sciences, 2019)
Cytochrome P450 2A6 (CYP2A6) substrate database constitute a potential class of disease related molecules as well as therapeutic molecules, primarily expressed in liver and lungs. The prediction of CYP2A6-related metabolism is of great interest. In this study, a docking protocol was presented which made use of poses of known substrate to help guide the configurational search and to rank predicted poses of test substrates. As a result, a 68% success rate was obtained. Predicting ideal configurations of compound would make significant impact on screening potential substrate, as the predicted bound conformations of 3 Tanshinone IIa (CYP2A6 substrate) analogues revealed differences among them and the inappropriate characteristic to be selected as substrates which was confirmed experimently.